ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PEMBELIAN PRODUK ORGANIK DI KOTA BATAM - Selly Celsya; Hepy Hefri Ariyanto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Customers interest in organic porducts continues to increase. Organic products that are processed without any chemical substances are trusted by the public as healthier and more nutritious products. This study aims to determine the factors that encourage customers to purchase organic products by using the theory of planned behavior as a basis for research. This study describes the extended TPB of attitude, which health consciousness, willingness to pay, trend and lifestyle as the added variable. Online survey was conducted on 460 respondents, by adopting purposive sampling approach. The data were analyzed using the Structural Equation Modeling (SEM) method, SPSS also used to test the CMV. Results showed that the relationship between health consciousness, willingness to pay and trend and lifestyle had a significant positive effect on attitude. Attitude, subjective norm and perceived behavioral control also had a significant positive effect on purchase intention. This research suggests retailers to develop effective marketing strategies in influencing consumers to buy organic products through advertising, promotion and new product development. Retail can also increase the availability of organic products to meet consumer demand.